Understanding the last Soviet generation : a critique of the historiography of the collapse of the Soviet union - Koh, Andy Ju Hua (2016)
In the immediate period after the collapse of the Soviet Union, the historiography was dominated by the absolute political arguments of the Cold War triumphalists. They argue that the Soviet collapse was unavoidable due to the inevitable Soviet economic failure and the American soft power winning over the hearts and minds of the Soviet masses. However, the premises of the triumphalistic arguments are questionable. This is because according to several sources which were published just before the collapse of the Soviet Union, the Soviet economic problems were not catastrophic. Also, the nationalist groups were not demanding for secession from the Soviet Union. Subsequently, the historiography has gradually shifted away from the lenses of Cold War triumphalism. For example, historians have adopted a social history approach to analyse the role of the masses and human agency in the Soviet collapse. Also, anthropologists have analysed the role of Mikhail Gorbachev in the Soviet collapse. Thus, the methods which are used to analyse the Soviet collapse have gradually shifted from the method of political science towards a broader range of methods which include the historical method and the anthropological method.